1992
DOI: 10.1111/j.1365-2729.1992.tb00408.x
|View full text |Cite
|
Sign up to set email alerts
|

IT in post‐graduate teacher training

Abstract: The IT capabilities expected of all students training to be teachers are now laid down in government guidelines but time on one year postgraduate courses is limited. It is therefore important to be aware of the IT skills that students bring with them to help develop the courses on offer. A questionnaire survey of nearly 400 PGCE primary and secondary students was completed for a 1989/90 cohort. This study set out to find what prior IT experience students brought with them, and what they perceived as their IT t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 6 publications
2
6
0
Order By: Relevance
“…The results, published in Baron & Bruillard, (1994a), concurred with those that were obtained in other countries (Dunn & Ridgway, 1991;Mellar & Jackson, 1992;Downes, 1993). They showed low levels of starting competencies, a rather high level of expectation towards IT as a pedagogical tool and difficulties in integrating IT in studies and in practical work.…”
Section: The Studysupporting
confidence: 79%
“…The results, published in Baron & Bruillard, (1994a), concurred with those that were obtained in other countries (Dunn & Ridgway, 1991;Mellar & Jackson, 1992;Downes, 1993). They showed low levels of starting competencies, a rather high level of expectation towards IT as a pedagogical tool and difficulties in integrating IT in studies and in practical work.…”
Section: The Studysupporting
confidence: 79%
“…However, these surveys concentrate mainly on whole cohorts and provide few insights into individual subject areas. One exception is Mellar & Jackson's 1992 article which reports differences in computer experience between subjects in a 1989-90 cohort of 230 secondary PGCE students: Their results showed that mathematics, science and geography students had greater experience than other subjects (a result which is in accord with* Summers's 1988-89 survey). Subjects where experience was particularly low included history and English.…”
Section: Surveys Of Student Teacherssupporting
confidence: 67%
“…Blackmore et al, 1992;Mellar & Jackson 1992, 1994. However, these surveys concentrate mainly on whole cohorts and provide few insights into individual subject areas.…”
Section: Surveys Of Student Teachersmentioning
confidence: 99%
“…In addition, over this period, monitoring in a number of countries has indicated that the levels of ICT skills of students on entry to higher education are steadily rising (Summers, 1990;Mellar & Jackson, 1992;Lienard, 1995) and in Scotland are now surprisingly high (Simpson et al, 1997), re¯ecting, amongst other things, the rapid advancement of the use of computers at home and in schools. This suggests that very soon, TEIs will be able to take for granted computer literacy in their incoming students, in the same way as they presently are able to rely on their attainment of adequate levels of numeracy and general literacy.…”
Section: Introductionmentioning
confidence: 97%